Supravalvar mitral ring with a parachute mitral valve and subcoarctation of the aorta in a child with hemodynamically significant VSD. A study of the morphology, echocardiographic diagnostics and surgical therapy - Mądry, Wojciech (J Ultrason, 2017)
The authors present a case of echocardiographic diagnosis of supravalvar mitral ring (a fibromembranous structure that arose from the atrial surface of the mitral leaflets) in a child with a parachute mitral valve, a ventricular septal defect, and mild narrowing of the aortic isthmus. The supravalvar mitral stenosis is a typical but very infrequently detected element of the complex of anatomical abnormalities located within the left heart and the proximal aorta, called the Shone’s complex (syndrome). Diagnosing an additional, hemodynamically significant anatomic defect during echocardiography was possible thanks to the detection of marked mobility limitation of the ring-adjacent part of the mitral valve mural leaflet as well as of an atypical image of turbulence occurring during the inflow from the left atrium to the left ventricle. The early diagnosis made it possible to perform complete correction of this complex congenital defect within a single operation.